1993
DOI: 10.1161/01.cir.88.2.381
|View full text |Cite
|
Sign up to set email alerts
|

LDL subclass phenotypes and the insulin resistance syndrome in women.

Abstract: Small, dense LDL is an integral feature of the insulin resistance syndrome. Nongenetic (ie, behavioral or environmental) factors are important for the expression of the phenotype and for its association with other heart disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
2
7

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(120 citation statements)
references
References 29 publications
(6 reference statements)
8
103
2
7
Order By: Relevance
“…Although the most common means of de®ning fat distribution and a good correlate of deep, abdominal fat, 7,32 it does not give as precise a description of abdominal fat distribution as more sophisticated techniques. 7,32 Nevertheless, within these limitations, the present and previous studies 15,16 have shown that the corrections can re®ne our perception of the relationship between body fat distribution and lipoproteins.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the most common means of de®ning fat distribution and a good correlate of deep, abdominal fat, 7,32 it does not give as precise a description of abdominal fat distribution as more sophisticated techniques. 7,32 Nevertheless, within these limitations, the present and previous studies 15,16 have shown that the corrections can re®ne our perception of the relationship between body fat distribution and lipoproteins.…”
Section: Discussionmentioning
confidence: 71%
“…Triglycerides have the strongest impact on the lipoprotein pro®le. 13,14 To our knowledge, only two studies, focusing on the LDL pro®le, have adjusted for triglycerides; in one 15 the presence of small, dense LDL was independently related to visceral fat accumulation, whilst the association was no longer signi®cant when corrected for triglycerides in a more recent study. 16 It thus remains unclear whether central obesity could in¯u-ence lipoprotein metabolism directly or via the agency of raised triglyceride levels.…”
Section: Introductionmentioning
confidence: 98%
“…16,17 Because WHR is frequently interpreted to indicate deposition of visceral fat, 9 this ®nding suggests a signi®cant relationship between visceral adiposity and LDL size phenotypes. Waist circumference also re¯ects visceral adiposity and may actually be a better indicator than WHR.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 ± 18 Moreover, LDL size phenotypes were signi®cantly associated with visceral adiposity, as estimated by WHR 14 ± 17 and also as directly measured by computed tomography. 18 In some of these studies, 16,17 WHR was more strongly associated with LDL size phenotype than was body-mass index (BMI), a global measure of adiposity. These results suggest that regional patterns of fat deposition might be differentially associated with dyslipidaemia and, perhaps, risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…7 -11 Adverse effects of insulin resistance on lipid metabolism, with consequent effects on circulating TAG concentrations, may be the primary metabolic defect that leads to low HDL and increased prevalence of small dense LDL, 12,13 which are the key features of the atherogenic lipoprotein phenotype. 14 Greater tendency for central fat deposition after the menopause may be particularly relevant to the higher incidence of CHD in post-menopausal women, since, although central obesity has been shown to be a strong risk factor for both men and women, studies in women generally produce values for relative risk that are higher than those found in men.…”
Section: Introductionmentioning
confidence: 99%